Slit2 inhibits SRC-PI3K signaling pathway, regulates osteoclast differentiation of macrophages and reduces bone resorption - Ge, Qing; Zou, Yaokun; Deng, Huizhi; Yang, Zhe; Ge, Linhu; Huang, Jieying; Cai, Jianqiang; Wang, Liping (Frontiers in Cell and Developmental Biology, 2025)
Osteoporosis is a metabolic disorder characterized by increased bone resorption and decreased bone formation. As a well-characterized axon guidance molecule, Slit2 contributes to central nervous system regulation by modulating intracellular signaling cascades and is expressed in multiple tissues, including the nervous system and the kidneys. However, limited research has explored the role of Slit2 in bone metabolism, and its precise regulatory mechanisms remain unclear. In this study, we established an aging-induced osteoporosis model using wild-type (WT) and Slit2-transgenic (Slit2-Tg) mice, as well as an estrogen-deficient ovariectomy-induced osteoporosis model. Our findings demonstrate that Slit2 attenuates bone loss and suppresses osteoclast differentiation under osteoporotic conditions. In vitro osteoclast differentiation assays further confirmed that Slit2 regulates osteoclast-associated marker expression and inhibits the differentiation of bone marrow-derived monocytes into osteoclasts. Mechanistically, RNA sequencing, Gene Ontology pathway enrichment analysis, and Western blotting revealed that Src and PI3K/AKT signaling pathways mediate the regulatory effects of Slit2 on bone metabolism. These findings suggest that Slit2 inhibits macrophage-to-osteoclast differentiation and attenuates bone resorption by downregulating Src expression in macrophages and suppressing the PI3K/AKT signaling pathway. This study provides novel insights into the therapeutic potential of Slit2 as a target for osteoporosis treatment.